Gastric perforation of late diagnosis - Benedetti, Juan L.; Pittamiglio, Horacio; Ferrari, Ivonne; Chavarría, Oscar (Cirugía del Uruguay, 1986)
Submitting for consideration a case of a three months old sucking baby presenting a gastric perforation of late diagnosis. In our opin1on, said late diagnosis was due to: rare ocurrence of this pathology; atypical presentation (as an abdominal tumor). Discussed are ethiological aspects, diagnostic procedures and related treatment.